I.- Euler / Lambert trinomial equations. Proof based on
Wang, Fei, Proof of a series solution for Euler’s trinomial equation, ACM Commun. Comput. Algebra 50, No. 4, 136-144 (2016). ZBL1370.33022.,
using Lagrange-Bürmann Theorem (LBT) to derive a series solution. (Technique is used below to solve the equation asked for)
The trinomial equation $$y = q + y^m$$ was solved in series form by Lambert, in 1758. Few years later, 1779, Euler transformed Lambert’s equation into the more symmetrical form with $y=x^{-\beta}$, $m=\alpha/\beta$ and $q=(\alpha-\beta)\cdot v$ as $$x^\alpha-x^\beta = (\alpha-\beta)\cdot v\cdot x^{\alpha+\beta}$$ so that $$v=f(x)=\frac{x^{-\beta}-x^{-\alpha}}{\alpha-\beta}$$ where $f(1)=0$ and $f'(1)=1$, therefore applying LBT $$x = 1+\sum_{n=1}^{\infty}\frac{v^n}{n!}\cdot[ \lim_{x\rightarrow1}\frac{d^{n-1}}{dx^{n-1}}\frac{(x-1)^n}{f(x)^n}]
$$ $$x = 1+\sum_{n=1}^{\infty}\frac{v^n(\alpha-\beta)^n}{n}\cdot \mathrm{res}_{x=1}\lbrack(x^{-\beta}-x^{-\alpha})^{-n}\rbrack$$ residues can be computed using some CAS (Wolfram or Maple). This gives $$x = 1+\sum_{n=1}^{\infty}\frac{v^n(\alpha-\beta)^n}{n}\cdot \frac{\prod_{j=1}^{n-1}[1+j\alpha+(n-j)\beta]}{(n-1)!(\alpha-\beta)^n}$$ finally, this expression can be written using Gamma functions or Binomials $$x = 1+\sum_{n=1}^{\infty}\frac{v^n(\alpha-\beta)^n}{n\alpha+1}\cdot \binom{(n\alpha+1)/(\alpha-\beta)}{n}$$ Lambert series is recovered with $\beta = -1$, $\alpha=-m$ and $x=y$, giving $$y = 1-\sum_{n=1}^{\infty}\frac{q^n}{nm-1}\cdot \binom{(nm-1)/(m-1)}{n}$$This series can be obtained directly in the same way using $q=g(y)=y-y^m$ and
computing the summand residues $\mathrm{res}_{y=1}[(y-y^m)^{-n}]$.
Both series can be represented as a special case of the generalized Fox-Wright Function $_k\Psi_ℓ^*(A;B;ζ)$ normalized such that $_k\Psi_ℓ^*(A;B;ζ)|_{ζ=0}=1$ (See this MO Answer here for details). $y$ series for $m\in \mathbb{R} \land m>1$ can be put as
$$y = -\frac{1}{m-1}\sum_{n=0}^{\infty}\frac{q^n}{n!}\cdot \frac{\Gamma(-\frac{1}{m-1}+n\cdot\frac{m}{m-1})}{\Gamma(1-\frac{1}{m-1}+n\cdot\frac{1}{m-1})}$$ which converges for $|q|<(m-1)m^{-\frac{m}{m-1}}$ giving $$y=\ _1\Psi_1^*([\frac{-1}{m-1},\frac{m}{m-1}];[1-\frac{1}{m-1},\frac{1}{m-1}];q)$$ A similar solution can be found in Section 4 of
Miller, A. R.; Moskowitz, I. S., Reduction of a class of Fox-Wright Psi functions for certain rational parameters, Comput. Math. Appl. 30, No. 11, 73-82 (1995). ZBL0839.33003.
and
Belkić, Dževad, All the trinomial roots, their powers and logarithms from the Lambert series, Bell polynomials and Fox-Wright function: illustration for genome multiplicity in survival of irradiated cells, J. Math. Chem. 57, No. 1, 59-106 (2019). ZBL1406.92284.
as well.
II.- A slight variation of this procedure allows to find the solution series for the specific problem asked for ($\gamma=2,\ n=2,\ m=5$) assuming $\gamma>0,\ m,n \in \mathbb{N},\ m>n$ $$z=\gamma\cdot\zeta^n-\zeta^m$$ We start from Ch 3 Bürmann's Theorem in
Sofo, Anthony, Computational techniques for the summation of series, New York, NY: Kluwer Academic/Plenum Publishers (ISBN 0-306-47805-6/hbk). xvi, 189 p. (2003). ZBL1059.65002.
Let $\phi(\zeta)$ be a simple function in a domain $\mathbb{D}$, zero at a point $a$ of $\mathbb{D}$, and let $$\vartheta(\zeta)=\frac{\zeta-a}{\phi(\zeta)},\ \ \vartheta(a)=\frac{1}{\phi'(a)}$$ If $f(\zeta)$ is analytic in $\mathbb{D}$ then $\forall \zeta \in \mathbb{D}$
$$f(\zeta)=f(a)+\sum_{k=1}^n \frac{[\phi(\zeta)]^k}{k!}\cdot \frac{d^{k-1}}{dt^{k-1}}[f'(t)\cdot[\vartheta(t)]^k]_{t=a}+R_{n+1}$$
$$f(\zeta)=f(a)+\sum_{k=1}^n \frac{[\phi(\zeta)]^k}{k}\cdot\mathrm{res}_{\,t=a}[f'(t)\cdot[\phi(t)]^{-k}]+R_{n+1}$$
This provides an expansion of a function in terms of series of powers of another function. Conditions for convergence can be seen in the given references. For now we can take it as a formal series. Using these relationships $$z=\phi(\zeta)=\gamma\cdot\zeta^n-\zeta^m,\ \ \ f(\zeta)=\zeta$$ The zeroes of $\phi(\zeta)$ are given by $m-n$ different roots $\zeta_\ell=\gamma^{\frac{1}{m-n}}\cdot\omega_{m-n}^\ell,\ \ \ell=0,1,..,m-n-1$ being $\omega_{k}$ the $k$-th root of unity and $\zeta_{m-n}=0$ with multiplicity $n$. Thus $$\zeta=\zeta_j+\sum_{k=1}^\infty \frac{z^k}{k}\cdot \mathrm{res}_{t=\zeta_j}[(\gamma\cdot t^n-t^m)^{-k}]$$ For example by taking $\gamma=2,\ n=2,\ m=5$. The root $\zeta_\mathrm{o}=2^{1/3}$ provides $$\zeta=2^\frac{1}{3}+\sum_{k=1}^\infty c_k z^k$$ whose first 10 terms $c_k$ are given by

The same procedure can be followed with every zero of $\phi(\zeta)$, giving different expansions.
III.- Another approach is to consider a solution based on Fox Wright series function. This MO link provides the inversion series that corresponds to a $_1\Psi_1^*$ function. For $\omega\in\mathbb{C},\ \alpha,\beta\in\mathbb{R}$ the general (standard) trinomial equation $$u-\omega\cdot u^\alpha-1=0$$ has the principal solution for $\alpha>1$ $$u =\,_{1}\Psi_{1}^{*}([1,\alpha];[2,\alpha-1];\omega)$$ whose powers satisfy $$u^\beta=\,_{1}\Psi_{1}^{*}([\beta,\alpha];[\beta+1,\alpha-1];\omega)$$ giving these series converging for $|w|<(\alpha-1)^{\alpha-1}\alpha^{-\alpha}$ $$u=\sum_{k=0}^{\infty}\frac{\omega^k}{k!}\cdot\frac{\Gamma(1+\alpha\cdot k)}{\Gamma(2+(\alpha-1)\cdot k)}$$ $$u^\beta=\beta\cdot\sum_{k=0}^{\infty}\frac{\omega^k}{k!}\cdot\frac{\Gamma(\beta+\alpha\cdot k)}{\Gamma(\beta+1+(\alpha-1)\cdot k)}$$ respectively. Since $\log{u}=\lim_{\beta\rightarrow 0}\frac{u^\beta-1}{\beta}$, logarithm series is obtained from this last series as well$$\log{u}=\sum_{k=1}^{\infty}\frac{\omega^k}{k!}\cdot\frac{\Gamma(\alpha\cdot k)}{\Gamma(1+(\alpha-1)\cdot k)}$$
The original problem $z=\gamma\cdot\zeta^n-\zeta^m$ can be worked now using simple algebra. Set $$u\cdot z =\gamma\cdot\zeta^n,\ \alpha=m/n,\ \omega=z^{-1}(z/\gamma)^\alpha\ \mathrm{and}\ \beta=1/n$$ This produces the Puiseux series (although it is also valid for $m,n\in\mathbb{R},\ \mathrm{s.t.}\ m>n>0$)$$\zeta=\frac{1}{n}(z/\gamma)^\frac{1}{n}\sum_{k=0}^{\infty}\frac{[z^{-1}(z/\gamma)^{\frac{m}{n}}]^k}{k!}\cdot\frac{\Gamma(\frac{1}{n}+\frac{m}{n}\cdot k)}{\Gamma(1+\frac{1}{n}+(\frac{m}{n}-1)\cdot k)}$$ Case $[m,n,\gamma]=[5,2,2]$, gives $$\zeta=\frac{1}{2}\sqrt{z/2}\sum_{k=0}^{\infty}\frac{(z/2)^{\frac{3}{2}k}}{2^k\,k!}\cdot\frac{\Gamma(\frac{1}{2}+\frac{5}{2}\cdot k)}{\Gamma(\frac{3}{2}+\frac{3}{2}\cdot k)}$$ converges for $0\le z\le (\frac{m}{n}-1)(\frac{\gamma\,n}{m})^\frac{m}{m-n}=1.034128651...$